Analisis Pengaruh Minat Belajar Siswa Terhadap Media Pembelajaran Berbasis Augmented Reality - Monita, Tisa; Sari, Ratih Dewi; Randikai, Madyus; Ibrahim, Ali (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
Teachers are required to package the subject matter to be more interesting, namely by developing interesting media and following technological developments, one of which is by utilizing Augmented Reality technology. Augmented Reality (AR) is a mixed concept of virtual reality and world reality. With augmented reality, we learn to use all aspects. Read, see and hear. With the hope that students can be interested in learning and can receive a good understanding of the lesson using AR. We here examine how much the influence of AR-based learning media to increase the interest in learning from these students.